Intragenomic conflict produces sex ratio dynamics that favor maternal sex ratio distorters. Issue 22 (15th October 2016) - Rood, Elaine S.; Freedberg, Steven
Abstract: Maternal sex ratio distorters (MSDs) are selfish elements that enhance their transmission by biasing their host's sex allocation in favor of females. While previous models have predicted that the female‐biased populations resulting from sex ratio distortion can benefit from enhanced productivity, these models neglect Fisherian selection for nuclear suppressors, an unrealistic assumption in most systems. We used individual‐based computer simulation modeling to explore the intragenomic conflict between sex ratio distorters and their suppressors and explored the impacts of these dynamics on population‐level competition between species characterized by MSDs and those lacking them. The conflict between distorters and suppressors was capable of producing large cyclical fluctuations in the population sex ratio and reproductive rate. Despite fitness costs associated with the distorters and suppressors, MSD populations often exhibited enhanced productivity and outcompeted non‐MSD populations in single and multiple‐population competition simulations. Notably, the conflict itself is beneficial to the success of populations, as sex ratio oscillations limit the competitive deficits associated with prolonged periods of male rarity. Although intragenomic conflict has been historically viewed as deleterious to populations, our results suggest that distorter–suppressor conflict can provide population‐level advantages, potentially helping to explain the persistence of sex ratio distorters in a range of taxa. Abstract : We used individual‐based computer simulation modeling to explore the intragenomic conflict between sex ratio distorters and their suppressors. We examined the impacts of these dynamics on population‐level competition between species characterized by MSDs and those lacking them. MSD populations often exhibited enhanced productivity and outcompeted non‐MSD populations, suggesting that distorter–suppressor conflict can provide population‐level advantages, potentially helping to explain the persistence of sex ratio distorters in a range of taxa.